2020
DOI: 10.1016/j.scitotenv.2020.141180
|View full text |Cite
|
Sign up to set email alerts
|

Electric fans: A potential stay-at-home cooling strategy during the COVID-19 pandemic this summer?

Abstract: Current public health guidance designed to protect individuals against extreme heat and the ongoing COVID-19 pandemic is seemingly discordant, yet during the northern hemisphere summer, we are faced with the imminent threat of their simultaneous existence. Here we examine the environmental limits of electric fan-use in the context of the United States summer as a potential stay-at-home cooling strategy that aligns with existing efforts to mitigate the spread of SARS-COV-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Sustainable indoor cooling approaches are urgently needed, including strong, enforced codes that mandate energy-efficient buildings, 159 a return to traditional tropical and subtropical building designs, 159 use of fans in climate zones where they provide effective cooling, 160 stringent minimum energy performance standards for air conditioners, 159 cool roofs (see panel 3), and increased urban green space (indicator 2.3.3).…”
Section: Indicator 213: City-level Climate Change Risk Assessmentsheadline Finding: In 2020 546 (81%) Of 670 Cities Reported Having Complmentioning
confidence: 99%
“…Sustainable indoor cooling approaches are urgently needed, including strong, enforced codes that mandate energy-efficient buildings, 159 a return to traditional tropical and subtropical building designs, 159 use of fans in climate zones where they provide effective cooling, 160 stringent minimum energy performance standards for air conditioners, 159 cool roofs (see panel 3), and increased urban green space (indicator 2.3.3).…”
Section: Indicator 213: City-level Climate Change Risk Assessmentsheadline Finding: In 2020 546 (81%) Of 670 Cities Reported Having Complmentioning
confidence: 99%
“…Additional studies in resting participants have found a net cooling effect of fans at 36 and 42 °C T a (Ravanelli et al, 2015 , 2017 ), with upper relative humidity limits of 80 and 50%, respectively (Ravanelli et al, 2015 , 2017 ). These limits are further extended with the addition of water spraying on the skin (Hospers et al, 2020 ). These studies indicate that (i) fans can provide a net cooling effect above current recommended limits and (ii) humidity must be considered when providing recommendations for public policy.…”
Section: Introductionmentioning
confidence: 99%
“…a Requirements are dependent on specific work setting and resources. strategies to mitigate thermal strain (Butts, et al, 2017;Casa et al, 2007;Chicas et al, 2020;DeMartini et al, 2011;Hospers et al, 2020;McDermott et al, 2009;Morris et al, 2016). It is important to note that whole-body cold-water immersion produces the most effective cooling rates; however, it lacks feasibility for implementation at the worksite (Casa et al, 2007).…”
Section: Current Researchmentioning
confidence: 99%